PENGEMBANGAN PROFESI GURU DALAM MENINGKATKAN KINERJA GURU - Muchamad Sifak Almurtadho; Moch Choirul Aris; Hanifatus Shoima; Yulia Rachmawati (BASA Journal of Language & Literature, 2021)
Abstract: Improving teacher performance to develop the teacher profession is very important in efforts to improve education in Indonesia. Indonesia which is now in the stage of developing countries must have high human resources. So it can be a developed country. In realizing this master is one of the professions that are very influential in improving human resources. But in this effort, there are many problems that exist in improving teacher performance. Teachers in Indonesia still can not be said to be professionals. Although it's not entirely. Efforts and solutions to overcome this already exist and have been structured. But implementation has not yet been done. So teachers only do chores with what's there.Keywords: Teachers, Professionality, Teacher Performance, Human Resources, Development